Case Report: Durable remission after abscopal effect following transcatheter hepatic arterial embolization in a patient with mucosal melanoma refractory to immunotherapy - Claus, Lynsey M.; Kostan, Hannah E.; Hicks, Marshall E.; Avritscher, Rony; Davies, Michael A. (Frontiers in Immunology, 2025)
Mucosal melanoma, a rare subtype of melanoma affecting mucosal surfaces, presents significant challenges in diagnosis and treatment, particularly due to its low programmed death-ligand 1 (PD-L1) expression and reduced response to immune checkpoint inhibitors (ICIs). This case report describes a 58-year-old woman with metastatic nasal mucosal melanoma initially resistant to neoadjuvant ipilimumab and nivolumab. After undergoing hepatic transcatheter arterial embolization, she experienced an unexpected abscopal effect, where distant metastases showed near-complete resolution despite prior lack of response to immunotherapy. The patient’s disease initially progressed despite two cycles of ICI treatment, and further immunotherapy with nivolumab and relatimab did not improve her condition. Subsequently, after bland embolization of a dominant hepatic mass, the patient received re-challenged combination immunotherapy with ipilimumab and nivolumab, leading to significant regression in metastatic sites including the liver, lungs, lymph nodes, and bones. This response contrasts with prior reports and highlights a potential mechanism by which embolization therapies may alter the immune microenvironment and enhance the efficacy of immunotherapy. The abscopal effect observed following local hepatic embolization may be attributed to tumor-induced immune activation, which is further amplified by ICI treatment. This case underscores the potential for integrating local embolization with immunotherapy to overcome resistance in metastatic melanoma, particularly in mucosal subtypes. Further research is necessary to elucidate the immune mechanisms underlying these responses and to optimize treatment strategies for melanoma patients.